MARKETING STRATEGY FOR INCREASING SALES OF COOKING OIL SHOES IN BAROKAH TRADING BUSINESS - I Nyoman Tri Sutaguna; Gusti Noorlitaria Achmad; Andriya Risdwiyanto; Muhammad Yusuf (International Journal of Economics and Management Research, 2023)
In every line of business, strategy is important because it is a series of decisions and actions directed at achieving company goals. More than that, entrepreneurs need a marketing strategy for their business. This is very important because it is a fundamental tool planned to achieve company goals by developing a sustainable competitive advantage through the markets entered and marketing programs used to serve target markets. This research conducted in UD. Barokah which is located in Jatinangor, Sumedang Regency. The phenomenon that occurs is that the monthly target set by the company is not achieved even though several strategies have been implemented. The purpose of this research is to find out the right marketing strategy in increasing the number of sales and being able to survive in the face of competition in basic cooking oil at UD. Barokah, Sumedang District. This research is a field research with a descriptive qualitative approach. Data is obtained from shop owners, employees, and regular customers. Methods of data collection by observation, interviews, and documentation. The approach used in this study is the SWOT analysis approach, which is the systematic identification of various factors to formulate corporate strategy. Based on the results of the analysis of the SWOT diagram and SWOT matrix, it can be seen that Barokah Trading Business is in quadrant I (Aggressive Strategy) and on the SO strategy, where the company's strengths and opportunities are greater than its weaknesses and threats. The SO strategy is the most appropriate strategy for UD. Barokah , while other strategies can be used as alternative strategies for reference and consideration that can develop and increase sales of Barokah Business Trade products . In addition, the Barokah Trading Business can also combine the ST strategy, WO strategy and WT strategy as needed to maximize the marketing strategy implemented. where the strengths and opportunities of the company are greater than the weaknesses and threats. The SO strategy is the most appropriate strategy for UD. Barokah , while other strategies can be used as alternative strategies for reference and consideration that can develop and increase sales of Barokah Business Trade products . In addition, the Barokah Trading Business can also combine the ST strategy, WO strategy and WT strategy as needed to maximize the marketing strategy implemented. where the strengths and opportunities of the company are greater than the weaknesses and threats. The SO strategy is the most appropriate strategy for UD. Barokah , while other strategies can be used as alternative strategies for reference and consideration that can develop and increase sales of Barokah Business Trade products . In addition, the Barokah Trading Business can also combine the ST strategy, WO strategy and WT strategy as needed to maximize the marketing strategy implemented.